2016
DOI: 10.1101/057323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulated forward and backward self motion, based on realistic parameters, causes strong motion induced blindness

Abstract: 11Motion Induced Blindness (MIB) is a well-established visual phenomenon whereby highly salient targets disappear when viewed against a moving background mask. No research has yet explored whether contracting and expanding optic flow can also trigger target disappearance. We explored MIB using mask speeds corresponding to driving at 35, 50, 65 and 80 km/h in simulated forward (expansion) and backward (contraction) motion as well as 2-D radial movement, random, and static mask motion types. Participants (n = 18… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 60 publications
(131 reference statements)
0
3
1
Order By: Relevance
“…Similar to our results, Geng et al (2007) reported stronger left biases in the lower compared to the upper visual field for the percentage and duration of disappearance in their focused-attention condition, but did so in two separate experiments with different observers. In contrast to the current study and Geng et al (2007), our group (Thomas et al, 2017) found a bias towards the upper visual fields,…”
Section: Lower Left Mib Target and Adhcontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar to our results, Geng et al (2007) reported stronger left biases in the lower compared to the upper visual field for the percentage and duration of disappearance in their focused-attention condition, but did so in two separate experiments with different observers. In contrast to the current study and Geng et al (2007), our group (Thomas et al, 2017) found a bias towards the upper visual fields,…”
Section: Lower Left Mib Target and Adhcontrasting
confidence: 99%
“…with the left bias failing to reach significance. Intriguingly, Thomas et al (2017) presented only one target on each trial in different locations on different trials, while Geng et al and our current study presented multiple targets within a single trial. We note that this is also consistent with (Bonneh et al, 2001) who also reported an upper (left) field bias, when they tested with a single target.…”
Section: Lower Left Mib Target and Adhmentioning
confidence: 59%
See 2 more Smart Citations